Studies on Pine Mycorrhiza in Nursery Seedlings - Thapar, H. S.; Paliwal, D. P. (Indian Forester, 1982)
The paper reports the observations made on status of mycorrhiza in pine nurseries of dome areas of Orissa, Andbra Pardesh and Madhya Pradesh and grasslands of Tamil Nodu. Mycorrhizal infections are categorised into seven forms. Presence of mycorrhiza in each nursery is compared with the nursery practices followed. The mycorrhizal development in general was found erratic and inadequate in most cases probably due to insufficient quantity of mycorrhizal soil or high pH.